2020
DOI: 10.1152/ajpcell.00509.2019
|View full text |Cite
|
Sign up to set email alerts
|

Copper promotes sheep pancreatic duct organoid growth by activation of an antioxidant protein 1-dependent MEK-ERK pathway

Abstract: Proper amounts of copper supplemented in livestock feed improve the physical growth and traits of farm animals. The pancreas is an important organ with both exocrine and endocrine portions. To investigate the role and mechanism of copper in the sheep pancreas, we first established sheep pancreatic duct organoids (sPDOs). We found that an appropriate amount of copper benefited the formation and growth of sPDOs, whereas excess or deficient copper damaged sPDOs. We found that the proliferation-stimulating effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 46 publications
(52 reference statements)
0
11
0
Order By: Relevance
“…Liu et al have established sheep pancreatic duct organoids to investigate the role and mechanism of copper in the sheep pancreas [90]. They showed that moderate concentrations of copper promote sheep pancreatic duct organoids and detailed the molecular mechanism through which copper induces the cell proliferation in the organoids.…”
Section: Sheepmentioning
confidence: 99%
“…Liu et al have established sheep pancreatic duct organoids to investigate the role and mechanism of copper in the sheep pancreas [90]. They showed that moderate concentrations of copper promote sheep pancreatic duct organoids and detailed the molecular mechanism through which copper induces the cell proliferation in the organoids.…”
Section: Sheepmentioning
confidence: 99%
“…Sheep pancreatic duct organoids were generated using pancreatic duct cells from healthy fetus ( 77 ). The organoid was cultured in Matrigel containing EGF, R-Spondin-1, FGF10, and Noggin in Wnt3a-conditioned medium ( 77 ), which is a similar system described in mouse ( 105 ).…”
Section: Development Of Farm and Companion Animal Organoid Models: Hi...mentioning
confidence: 99%
“…Sheep pancreatic duct organoids were generated using pancreatic duct cells from healthy fetus ( 77 ). The organoid was cultured in Matrigel containing EGF, R-Spondin-1, FGF10, and Noggin in Wnt3a-conditioned medium ( 77 ), which is a similar system described in mouse ( 105 ). Furthermore, this study demonstrated an importance of an appropriate amount of copper supplementation to the medium in order to achieve formation and growth of sheep pancreatic duct organoids ( 77 ).…”
Section: Development Of Farm and Companion Animal Organoid Models: Hi...mentioning
confidence: 99%
See 1 more Smart Citation
“…These include canine organoids from the skin ( Wiener et al, 2018 ), prostate gland ( Usui et al, 2017 ), urinary bladder ( Elbadawy et al, 2019 ), kidney ( Chen et al, 2019 ) and liver ( Nantasanti et al, 2015 ), as well as porcine organoids from the esophagus submucosal gland ( von Furstenberg et al, 2017 ), rectum ( Adegbola et al, 2017 ), and testicle ( Sakib et al, 2019 ; Vermeulen et al, 2019 ). It also includes those from the mammary gland, pancreatic duct, and endometrium in cattle ( Martignani et al, 2018 ), sheep ( Liu et al, 2020 ) and horse ( Thompson et al, 2020 ), respectively. Notably, no respiratory or lung organoids have been reported in animals.…”
Section: Organoids: the Culturable Mini-organs In Humans And Animalsmentioning
confidence: 99%